2011
DOI: 10.1016/j.matbio.2010.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Collagen binding specificity of the discoidin domain receptors: Binding sites on collagens II and III and molecular determinants for collagen IV recognition by DDR1

Abstract: The discoidin domain receptors, DDR1 and DDR2 are cell surface receptor tyrosine kinases that are activated by triple-helical collagen. While normal DDR signalling regulates fundamental cellular processes, aberrant DDR signalling is associated with several human diseases. We previously identified GVMGFO (O is hydroxyproline) as a major DDR2 binding site in collagens I–III, and located two additional DDR2 binding sites in collagen II. Here we extend these studies to the homologous DDR1 and the identification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
177
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 168 publications
(185 citation statements)
references
References 38 publications
5
177
0
3
Order By: Relevance
“…Detailed investigations have established relative specificity with respect to DDR-binding to alternate, non-fibrillar collagens such as the collagens IV and X and have also revealed that such specificity is defined by nonconserved residues located at the periphery of the binding trench [26]. Such investigations provide a framework by which to elaborate the detailed collagen-binding properties of CPX-1, CPX-2 and ACLP.…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…Detailed investigations have established relative specificity with respect to DDR-binding to alternate, non-fibrillar collagens such as the collagens IV and X and have also revealed that such specificity is defined by nonconserved residues located at the periphery of the binding trench [26]. Such investigations provide a framework by which to elaborate the detailed collagen-binding properties of CPX-1, CPX-2 and ACLP.…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…Collagen types I and III are the predominant isoforms found in the lungs (27,28), though types IV and V are also expressed (29) and are critical for lung homeostasis. Intact type IV and V collagens interact with integrins (30), matricellular proteins (31), and discoidin receptor (32) in normal physiology.…”
Section: Evolution and Remodeling Of The Ecmmentioning
confidence: 99%
“…The VWF-binding site on collagen III was located to residues 572-580 of the collagen III α1 chain (8). The core VWF-binding sequence, RGQOGVMGF, is 100% conserved in collagens II and III and this motif also forms a binding site for the matrix protein SPARC (also known as osteonectin) (9) and discoidin domain receptors 1 and 2 (DDR1 and DDR2) (10,11). Interestingly, although collagen I is a good ligand for VWF, the VWF-binding sequence is only partially conserved in collagen I. Collagen I, unlike collagen III, is a heterotrimeric collagen consisting of two α1(I) chains and one α2(I) chain, where the collagen chain register, i.e., the relative position of the α2 chain in the heterotrimer, is unknown.…”
mentioning
confidence: 99%